6-2(x+8)=6x-26

Simple and best practice solution for 6-2(x+8)=6x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(x+8)=6x-26 equation:


Simplifying
6 + -2(x + 8) = 6x + -26

Reorder the terms:
6 + -2(8 + x) = 6x + -26
6 + (8 * -2 + x * -2) = 6x + -26
6 + (-16 + -2x) = 6x + -26

Combine like terms: 6 + -16 = -10
-10 + -2x = 6x + -26

Reorder the terms:
-10 + -2x = -26 + 6x

Solving
-10 + -2x = -26 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-10 + -2x + -6x = -26 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-10 + -8x = -26 + 6x + -6x

Combine like terms: 6x + -6x = 0
-10 + -8x = -26 + 0
-10 + -8x = -26

Add '10' to each side of the equation.
-10 + 10 + -8x = -26 + 10

Combine like terms: -10 + 10 = 0
0 + -8x = -26 + 10
-8x = -26 + 10

Combine like terms: -26 + 10 = -16
-8x = -16

Divide each side by '-8'.
x = 2

Simplifying
x = 2

See similar equations:

| 5(2-7)-y=2(y+1) | | 45+5x=5 | | X+(x-4)+2(x-4)=24 | | y+2.5=.5 | | 5=5x+45 | | 4z+9=-9 | | 7z+8=64 | | 6+18=-y+11 | | 30=q-31 | | 1z+8=13 | | W-7=19 | | 1+1(4X*5)= | | 2=n-96 | | 1y+8=13 | | T-38=53 | | 4f=72 | | 4=p-4 | | 2z=4.8 | | 2x-9=3(x-9) | | 10x-3+77= | | -9t/14-t/7=1 | | 17.78=g+8.13 | | 9=3/4e;e=12 | | x^3=-27m^18n^12 | | C/3=4.2 | | -(x+1)=1 | | 6/8=60/u | | 14000= | | I/3h=6;h=2 | | (n/2)-8=-2 | | 23x+17y=4 | | 4x+y+2x+y+8x+y=180 |

Equations solver categories